Penzonasian Mangrove Dan Keterkaitannya Dengan Salinitas Di Muara Sungai Upang Kabupaten Banyuasin Sumatera Selatan - Hendro H Sinaga; Heron Surbakti; Gusti Diansyah (Faculty of Mathtmatics and Natural Sciences, 2019)
The mangrove is a plant native to tropical areas in the coastal area of Indonesia. This research aims to analyze the distribution of salinity in Upang River Estuary, to determine the density, relative frequency and dominance of mangrove in Upang Estuaries River Banyuasin Regency South Sumatera, to determine the zonation of mangrove in Upang River Estuary Banyuasin Regency South Sumatera, to analyse the relation between salinity with mangrove zonation in Upang River Estuary anyuasin Regency South Sumatera. This Research was carried out in October 2015. The metodhs used for analysis of mangrove were density type, Relative Density (RD), the Relative Frequency (RF), Relative Dominance (RD), and important values’s index and the analysis of physics chemistry factors using the ODV. Salinity values at high and low tide conditions ranged from 12,5 – 25 PSU and 15 – 20 PSU respeclively. In the phases of the tree kind of Avicennia marina had the highest density of 1567 ind/ha with 300% of INP. In the phase of sampling type Avicennia marina and Sonneratia alba had the same highest density of 800 ind/ha with 300% of INP for both. In the Phase for seed type Sonneratia alba had the highest density of 23,333 ind/ha with 200% of INP. Zoning formed in Upang River Estuary was Avicennia marina, Sonneratia alba, Nypa fruticans and Avicennia marina.